Laboratory and semi-field evaluations on lethal and residual effects of temephos and pyriproxyfen insecticides to control malaria mosquito larvae, Anopheles stephensi Liston - Kourosh Azizi; Aboozar Soltani; Shokat Ali Amiri; Mohammad Reza Fakoor Ziba; Mohammad Djaefar Moemenbellah-Fard (Shiraz University of Medical Sciences, 2019)
Background: The application of insecticides against vector mosquito larvae is a crucial step to control human malaria. Insecticide resistance is a major impediment to vector control strategies. The main aim of this study was to conduct laboratory and semi-field evaluations on lethal and residual effects of temephos and pyriproxyfen insecticides against malaria mosquito larvae, Anopheles stephensi. Methods: Both susceptibility test and residual bioassay were performed to assess the lethal concentrations of each insecticide on 50% (LC50) of the IV instars larval populations and their activity periods according to standard protocols of WHO. Nine and eleven different concentrations with two sets of control in each case were applied for temephos and pyriproxyfen, respectively. Data were analyzed using probit analysis and SPSS software. Results: The LC50 and LC90 for temephos and pyriproxyfen under laboratory conditions were 0.4 and 0.63, and 1.69 × 10-4 and 4.036 × 10-4 ppm, respectively. Although the field strain of An. stephensi larvae was completely susceptible to pyriproxyfen, there was noticeable resistance (8% mortality at the diagnostic dose) to temephos in Nikshahr County, Southeast Iran. This is the first report of resistance to temephos for this malaria main vector in Iran. Depending on the applied variable doses, the residual effects of temephos and pyriproxyfen under semi-field conditions lasted maximally for 3 and 10 weeks, respectively. Conclusion: The high lethal and residual effects of pyriproxyfen on mosquito larvae confer an unprecedented opportunity in vector control operations leading to elimination of malaria in Iran.